2010
DOI: 10.1093/jac/dkq303
|View full text |Cite
|
Sign up to set email alerts
|

Spondylodiscitis: update on diagnosis and management

Abstract: Spondylodiscitis, a term encompassing vertebral osteomyelitis, spondylitis and discitis, is the main manifestation of haematogenous osteomyelitis in patients aged over 50 years. Staphylococcus aureus is the predominant pathogen, accounting for about half of non-tuberculous cases. Diagnosis is difficult and often delayed or missed due to the rarity of the disease and the high frequency of low back pain in the general population. In this review of the published literature, we found no randomized trials on treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
827
8
76

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 523 publications
(942 citation statements)
references
References 167 publications
31
827
8
76
Order By: Relevance
“…Twelve patients needed surgery, and thus conservative treatment failed in 13.1 % of patients. Karadimas et al [12] noted 17.1 % failures among patients managed non-surgically; other authors have reported failure rates from 12 to 16 % [1,4,7]. We had three in-hospital deaths in this group.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Twelve patients needed surgery, and thus conservative treatment failed in 13.1 % of patients. Karadimas et al [12] noted 17.1 % failures among patients managed non-surgically; other authors have reported failure rates from 12 to 16 % [1,4,7]. We had three in-hospital deaths in this group.…”
Section: Discussionmentioning
confidence: 52%
“…Consensus regarding the diagnosis exists. A combination of history, clinical, laboratory and microbiological findings are crucial, and MRI has become the imaging modality of choice [7]. Contrary to diagnostics, treatment measures are still widely discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aetiologically, spinal infection can be classified as pyogenic, granulomatous (tuberculosis, brucellosis, or fungal infection) or parasitic. Although improvements in surgical and radiological techniques together with modern antimicrobial therapy have dramatically diminished the morbidity and mortality of the disease, no well-designed randomised trial for its treatment has been published, although spinal surgical infections have been covered [23]. Furthermore, its incidence, although rare, is increasing up to four to 24 cases per million per year due to better diagnosis [33], intravenous drug use, a rise in health care-associated infection, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal spondylitic tuberculosis diagnosis can be confirmed by the polymerase chain reaction (PCR) [29], and molecular diagnostic methods using broad-range 16S rDNA PCR are also especially useful in the context of prior antibiotic use or the presence of fastidious micro-organisms. Species-specific PCR, particularly targeting Staphylococcus aureus, can increase the sensitivity further with the additional benefit of providing methicillin susceptibility results by amplification of the mecA gene [23]. However, 16S rDNA PCR is inferior to culture at detecting mixed organisms due to preferential primer binding, and care should be taken in interpreting all results when deciding on antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%